ISLAMIC EDUCATION UNDER STATE LAW: NEGOTIATING GOVERNANCE, AUTONOMY, AND PEDAGOGICAL IDENTITY - Anshori, Ibnu; Sasmitaningtyas, Elmi (Four Son Scholarship, 2025)
Islamic education operates within increasingly complex legal and governance frameworks shaped by state regulation, accountability demands, and educational standardization. While state law aims to ensure institutional legitimacy and quality assurance, it simultaneously raises questions regarding autonomy and the preservation of pedagogical identity within Islamic educational institutions. This study examines how Islamic education negotiates governance, autonomy, and pedagogical identity under state law through a qualitative library-based research approach. Drawing on scholarly literature, policy documents, and legal texts related to Islamic education and educational governance, the study employs thematic analysis to explore patterns of regulatory adaptation and institutional response. The findings reveal that governance in Islamic education is best understood as a negotiated process rather than a unilateral exercise of state control. Islamic educational institutions tend to adopt selective administrative compliance to meet legal requirements while maintaining substantive autonomy in pedagogical and moral domains. Autonomy emerges as relational and context-dependent, shaped by ongoing interactions between state regulation, institutional leadership, and religious tradition. Pedagogical identity proves to be the most resilient dimension of autonomy, largely sustained through internal leadership authority and the reinterpretation of regulatory frameworks. The study contributes theoretically by advancing the concept of negotiated governance in the context of Islamic education, challenging binary views of regulation versus autonomy. From a policy perspective, the findings suggest that adaptive and dialogical regulatory approaches are more effective in supporting educational quality and institutional sustainability. Overall, this study positions Islamic education as an active educational actor capable of engaging constructively with state law while safeguarding its pedagogical distinctiveness.